2018
DOI: 10.1007/s00415-018-9064-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers to help-seeking for sexual dysfunction in multiple sclerosis

Abstract: Barriers to discussing SD are similar between patients and HCPs. The most common barriers are addressable through modifications in the clinic environment, raising awareness and providing training opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Both patients and healthcare professionals find it difficult to broach sexual dysfunction in the clinic; having family or friends in the room is an important impeding factor. Other key barriers for patients include the priority of other neurological symptoms and that sexual problems are not often enquired about during the conversation, whereas healthcare professionals report a lack of knowledge in the field and inadequate time during the appointment 6. To provide a more conducive setting for initiating a discussion about sexual difficulties, clinicians should provide an opportunity for the patient to be seen alone in a safe and confidential environment.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Both patients and healthcare professionals find it difficult to broach sexual dysfunction in the clinic; having family or friends in the room is an important impeding factor. Other key barriers for patients include the priority of other neurological symptoms and that sexual problems are not often enquired about during the conversation, whereas healthcare professionals report a lack of knowledge in the field and inadequate time during the appointment 6. To provide a more conducive setting for initiating a discussion about sexual difficulties, clinicians should provide an opportunity for the patient to be seen alone in a safe and confidential environment.…”
Section: Assessmentmentioning
confidence: 99%
“…Embarrassment is an important barrier to addressing this topic for both healthcare professionals and patients 6. It can help first to enquire about less embarrassing pelvic organ complaints, such as bladder and bowel dysfunction, before stating that sexual problems also occur and asking if they would like to discuss this.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reasons that health care providers are unable to address sexual function in this community including presence of family or friends, not being asked, and inadequate time during the clinical visits [ 6 ]. However, recently we are witnessing growing concern on sexual dysfunction in women with multiple sclerosis especially among women with younger age.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason could be the barriers for people with MS and health care professionals to talk about intimacy and sexual dysfunction. A recent study 22 found that the most common barriers reported by patients were the perceived dominance of neurologic symptoms, the presence of family or friends, and not being asked. Barriers reported by health care professionals were the presence of family or friends, lack of knowledge about sexual dysfunction, and inadequate time during the consultation.…”
mentioning
confidence: 99%